Comparative study on the teacher-librarian collaboration program of level II PAASCU accredited schools in Quezon City - Castillo, Neowy Lindsay G. (2014)
Teachers and librarians are instructional partners. They both have corresponding roles which are integral to a school's success. In theory, teacher librarian collaboration has a positive impact not only to the students, but to the teachers and librarians as well. With the librarian and teachers jointly planning and monitoring instruction, the needs of the students will be more effectively met. Teachers and librarians are instructional partners. They both have corresponding roles which are integral to a school's success. In theory, teacher librarian collaboration has a positive impact not only to the students, but to the teachers and librarians as well. With the librarian and teachers jointly planning and monitoring instruction, the needs of the students will be more effectively met.